A planar wideband microstrip patch antenna for UHF RFID tag - Bashri, M. S. R.; Ibrahimy, Muhammad Ibn; Motakabber, S. M. A. (2013)
In this research, a planar wideband microstrip patch antenna for passive radio frequency identification (RFID) tag is proposed. To enable universal operation by covering the operating frequency of ultra-high frequency (UHF) RFID band from 860 MHz to 960 MHz, two C-shaped patches are employed. Both of the patches are inductively coupled fed by a rectangular loop feeding network for complex impedance matching with the referenced microchip impedance. The proposed antenna is designed for tagging metallic objects. To simplify the fabrication process and to reduce cost, a planar antenna structure is chosen over multi or cross layered configuration. The simulation and measurement results show impedance bandwidth of 159 MHz and 155 MHz (Return loss ≥ 3 dB) respectively when mounted on metal plate.